The Relationship between Haqīqat al-Insān and Modern Social Theory - Saluran; Asti Hani Marselina; Farhan (Penerbit Hellow Pustaka, 2025)
This research aims to analyze the relevance of the concept of Haqiiqatul Insan within the framework of modern social theory, bridging the understanding of Islamic spirituality with contemporary sociology. Employing a comprehensive literature review research design, this study examines various primary and secondary sources from classical Islamic literature and modern social theory. The main findings indicate that the concept of Haqiiqatul Insan, which emphasizes the human essence as a spiritual and moral being, offers a unique perspective to address the limitations of modern social theories that tend to be materialistic and reductionist in understanding the human dimension. The implications of this research are highly significant, paving the way for the development of new interdisciplinary approaches that integrate spiritual insights into social analysis, thereby enriching the understanding of human behavior and societal structures. Practically, this can inform more holistic social policies and the development of community interventions rooted in universal human values. The originality of this research lies in its systematic effort to build a dialogue between the rich Islamic intellectual tradition and the dominant discourse of modern social theory, offering a novel conceptual framework largely unexplored in sociological literature.